The birth of cardiac disease: Mechanisms linking gestational diabetes mellitus and early onset of cardiovascular disease in offspring - Tocantins, Carolina (2022)
Cardiovascular disease (CVD) is the biggest killer worldwide, composing a major economic burden for health care systems. Obesity and diabetes are dual epidemics on the rise and major risk factors predisposing for CVD. Increased obesity- and diabetes-related incidence is now observed among children, adolescents, and young adults. Gestational diabetes mellitus (GDM) is the most common metabolic pregnancy disorder, and its prevalence is rapidly increasing. During pregnancies complicated by GDM, the offspring are exposed to a compromised intrauterine environment characterized by hyperglycemic periods. Unfavorable in utero conditions at critical periods of fetal cardiac development can produce developmental adaptations that remodel the cardiovascular system in a way that can contribute to adult-onset of heart disease due to the programming during fetal life. Epidemiological studies have reported increased cardiovascular complications among GDM-descendants, highlighting the urgent need to investigate and understand the mechanisms modulated during fetal development of in utero GDM-exposed offspring that predispose an individual to increased CVD during life. In this manuscript, we overview previous studies in this area and gather evidence linking GDM and CVD development in the offspring, providing new insights on novel mechanisms contributing to offspring CVD programming by GDM, from the role of maternal-fetal interactions to their impact on fetal cardiovascular development, how the perpetuation of cardiac programming is maintained in postnatal life, and advance the intergenerational implications contributing to increased CVD premature origin. Understanding the perpetuation of CVD can be the first step to manage and reverse this leading cause of morbidity and mortality. This article is categorized under: Reproductive System Diseases > Molecular and Cellular Physiology Cardiovascular Diseases > Molecular and Cellular Physiology Metabolic Diseases > Genetics/Genomics/Epigenetics.